2014
DOI: 10.1002/mc.22223
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase A mediates c‐Myc's oncogenic effects in hepatocellular carcinoma

Abstract: Dysregulation of c-Myc (Myc) has been shown to contribute to progression of hepatocellular carcinoma, however, the detailed molecular mechanism remains poorly understood. Here, we report that Myc binds to the Aurora kinase A (Aurka) promoter and induces expression of Aurka in HCC cells. Increased expression of Aurka correlates with that of Myc in HCC. Nuclear accumulation of Aurka was confirmed by subcellular protein fractionation and immunoblot experiments in HCC cells. Myc inhibition decreases the nuclear ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…For instance, AURKA stimulates telomerase activity by upregulating Myc in human ovarian and breast epithelial cells [43]. Destruction of AURKA or Myc inhibits the malignant phenotypes of hepatocellular carcinoma cells [32]. In agreement with previously published articles, our results showed that there was a direct correlation with c-Myc expression and AURK, and both were suppressed by rhBMP-2 in gastric cancer cells.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…For instance, AURKA stimulates telomerase activity by upregulating Myc in human ovarian and breast epithelial cells [43]. Destruction of AURKA or Myc inhibits the malignant phenotypes of hepatocellular carcinoma cells [32]. In agreement with previously published articles, our results showed that there was a direct correlation with c-Myc expression and AURK, and both were suppressed by rhBMP-2 in gastric cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…We validated c-Myc expression after treatment with rhBMP-2 by qPCR and western blot assay; we found that c-Myc expression was significantly suppressed by rhBMP-2 treatment in both types of gastric cancer cells. Myc is recognized as a crucial oncogene in many types of human cancers, including gastric cancer [3234]. Therefore, the downregulation of c-Myc by rhBMP-2 might be responsible for the inhibition of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though demonstrated in breast cancer models, this concept has important implications given a potential relationship between Aurora A kinase and Myc, as demonstrated in various Myc-driven malignancies including hepatocellular carcinoma and B-cell lymphomas (Den Hollander et al, 2010; Lu et al, 2014). In both tumor types, Myc has been found to induce Aurora A kinase, and thus it may be hypothesized that the more synergistic combination effects demonstrated in select CRC models could be due to MEK inhibitor mediated degradation of c-Myc leading to more robust effects on Aurora A.…”
Section: Discussionmentioning
confidence: 99%